Country Concepts and the Rational Actor Trap - Limitations to Strategic Management of International NGOs - Dirk Kohnert (ZBW - Leibniz Information Centre for Economics; ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2004)
Growing criticism of inefficient development aid demanded new planning instruments of donors, including international NGOs (INGOs). A reorientation from isolated project-planning towards holistic country concepts and the increasing rationality of a result-orientated planning process were seen as answer. However, whether these country concepts – newly introduced by major INGOs too - have increased the efficiency of development cooperation is open to question. Firstly, there have been counteracting external factors, like the globalization of the aid business, that demanded structural changes in the composition of INGO portfolios towards growing short-term humanitarian aid; this was hardly compatible with the requirements of medium-term country planning. Secondly, the underlying vision of rationality as a remedy for the major ills of development aid was in itself a fallacy. A major change in the methodology of planning, closely connected with a shift of emphasis in the approach to development cooperation, away from project planning and service delivery, towards supporting the socio-cultural and political environment of the recipient communities, demands a reorientation of aid management: The most urgent change needed is by donors, away from the blinkers of result-orientated planning towards participative organizational cultures of learning. – – Les `concepts de pays' et le piège de l'acteur rationnel - limites de la gestion stratégique des ONG internationales: Des critiques croissantes de l'aide au développement inefficace exigent de nouveaux instruments de planification des bailleurs de fonds, y compris les ONG internationales (ONGI). Une réorientation de la planification des projets isolés vers des concepts holistiques de la planification de l'aide par pays ainsi que la rationalité croissante d'un processus de planification orientée vers les résultats ont été considérés comme réponse. Toutefois, si ces concepts de pays - nouvellement introduites par les grandes OING eux aussi - ont augmenté l'efficacité de la coopération au développement est ouvert à la question. Tout d'abord, il y a eu l'impact des facteurs externes, comme la mondialisation de l'entreprise de l'aide, qui a exigé des changements structurels dans la composition des portefeuilles des OING vers la croissance de l'aide humanitaire à court terme. Cela était difficilement compatible avec les exigences de l'aménagement du territoire à moyen terme. Deuxièmement, la vision sous-jacente de la rationalité accrue de la planification, concentré sur les resultats, comme un remède pour les grands maux de l'aide au développement était en soi une erreur. Un changement majeur dans la méthodologie de la planification, étroitement liée à un changement d'orientation dans l'approche de la coopération au développement, qui n'est pas concentrer sur planification du projet et la prestation de services, mais qui soutienne l'environnement socio-culturel et politique des communautés bénéficiaires, exige une réorientation de la gestion de l'aide: Le changement le plus urgent est un changement par les donateurs eux-mêmes, qui devrait implanter des cultures de collaboration étroit avec les partenaires et la population locale.
Conference: Annual Conference of the Research Committee for Developing Countries, Verein für Socialpolitik, Cologne, July 2-3, 2004; Additional information: Author's version.
Keywords: L3; O2; F35; L31; 330; country concepts; development planning; NGOs; project planning; Sub-Saharan Africa; Länderkonzepte; Entwicklungshilfe; Nichtregierungsorganisation; Entwicklungsplanung